Finding her voice: first class female sexuality. Issue 2 (2nd April 2016) - McCarthy, Barry; Wald, Lana M.
ABSTRACT: The focus of this clinical paper is twofold: (1) the equity model of female–male sexuality and (2) female sexuality as first class and that it is more variable, flexible, complex, and individualistic than male sexuality. We explore issues of desire, orgasm, and pain within the context of healthy female sexuality. Furthermore, we provide examples of how women and men, being intimate and erotic allies, promote healthy sexuality for the woman, man, couple, and culture.